Association Between the MUC5B Promoter Polymorphism rs35705950 and Idiopathic Pulmonary Fibrosis: A Meta-analysis and Trial Sequential Analysis in Caucasian and Asian Populations. Issue 43 (October 2015) - Zhu, Qing-Qing; Zhang, Xin-Lin; Zhang, Si-Min; Tang, Shao-Wen; Min, Hai-Yan; Yi, Long; Xu, Biao; ,; Song, Yong
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive disease with a poor prognosis. A number of studies reported the association between MUC5B promoter polymorphism rs35705950 and IPF, but substantial inconsistent findings were observed and the strength of association remains unclear. The aim of the study was to investigate the association between rs35705950 and IPF in different ethnic populations. PubMed, EMBASE, Web of Science, and CENTRAL were searched from their inception to April 15, 2015. Allelic and phenotypic comparisons were conducted separately, as were comparisons in Caucasian and Asian populations. A meta-analysis with trial sequential analysis was conducted. Nine studies presented in 7 full-text articles were included, encompassing 2733 IPF patients and 5044 controls. Six studies were carried out in the Caucasian population, and 3 in the Asian population. Minor T allele was associated with an increased risk of IPF compared with G allele (odds ratio [OR] 4.85, 95% confidence interval [CI] 3.79–6.21, P = 5.88 × 10 −36 ), as were TG and TT genotypes compared with GG genotype (TG vs GG: OR 6.20, 95% CI 5.14–7.48, P = 1.70 × 10 −81 ; TT vs GG: OR 11.29, 95% CI 5.69–22.40, P = 4.22 × 10 −12 ), in an allele dose-dependent manner. These observations were confirmed in trial sequential analysis in both populations. The strength of association was more remarkable in the Caucasian population than in the Asian population, and no homozygous TT genotype was detected in the Asian population in our study. Our study revealed strong association between the MUC5B promoter rs35705950 polymorphism and the risk of IPF. The strength of association between rs35705950 minor T allele and IPF susceptibility was particularly evident in the Caucasian population, and milder but still significant in the Asian population.